Comparison of ultrasound-based measures of inferior vena cava and internal jugular vein for prediction of hypotension during induction of general anesthesia - Dalia Khaled; Ismail Fathy; Yasser M. Elhalafawy; Dina Zakaria; Islam Rasmy (Egyptian Journal of Anaesthesia, 2023)
ABSTRACTBackground Hypotension after GA induction may induce organ injury. Ultrasonographic IVC and IJV studies for intravascular volume assessment and hypotension prediction were established. This study compared between them in prolonged hypotension during induction of GA prediction.Methods One-hundred sixty three adult patients, of ASA physical status I & II, for elective surgery under GA were screened. One hundred thirty three patients were included. Preoperative ultrasonographic IVC parameters (dIVC max, dIVC min & CI) and IJV parameters (IJV area in supine and Trendelenberg positions & IJV change rate) measurements were recorded with baseline MBP. After anesthetics administration, MBP was recorded every minute for 15 minutes. Intubation was established after 3 minutes. Study used hypotension definition as over 20% decrease from baseline MBP. Prolonged hypotension definition used was hypotension duration ≥ 2 minutes. Severe hypotension definition used was decreased MBP from baseline value over 40%.Results Six patients didn’t satisfy inclusion criteria; seventeen patients showed low IVC visualization and 133 patients were involved. The prolonged hypotension after GA induction incidence was 63.2% (84 patients), while severe hypotension incidence was 9% (12 patients). IJV change rate > 0.28 predicted prolonged post-induction hypotension with specificity 76% (95% confidence interval, 61–87%) and sensitivity 55% (95% confidence interval, 44–66%). IJV change rate > 0.35 predicted severe post-induction hypotension with specificity 72% (95% confidence interval, 63–80%) and sensitivity 75% (95% confidence interval, 43–95%). Alternatively, no IVC measure reliably estimated prolonged or severe post-induction hypotension.Conclusion IJV surpasses IVC in prolonged post-induction hypotension prediction with moderate predictive value.